The metabolic demand of external load carriage in golfers: a comparison of a single versus double-strap golf bag - Holland, C. J.; Godwin, M. S. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: A golf bag filled with a set of clubs provides a substantial load. When carried over distance this can increase the demands placed upon the golfer, leading to discomfort, fatigue and injuries. This study aimed to compare the metabolic demands of 2 methods of golf bag carriage. METHODS: A total of 16 healthy male recreational golfers participated in the study. Participants were given an initial familiarization session in which their self-selected walking speed was determined. This was utilized as the treadmill speed for all subsequent trials. The testing protocol consisted of 3 randomized trials of treadmill walking for 5 minutes in each of three conditions: unloaded, single-strap bag and double-strap bag. Equipment consisted of a double-strap golf bag with a standard set of clubs weighing 12.5kg. For all trials oxygen consumption (L/min), VO2 (mL·kg/min) respiratory minute volume (VE) (L/min), and heart rate (HR) were measured. RESULTS: Results showed that the double-strap bag required significantly less oxygen consumption (1.19±0.19 vs. 1.31±0.16 L/min, P<0.01) relative oxygen consumption (14.49±2.06 vs. 15.93±2.25 mL·kg/min, P<0.01), reduced respiratory minute volume (29.95±4.19 vs. 32.47±4.26 L/min, P<0.05), and lower heart rates (100.14±11.05 vs. 106.96±9.33 BPM, P<0.001) than the single-strap bag. Both methods of carriage showed significantly greater metabolic demands than the unloaded condition (P<0.05). CONCLUSIONS: The decreased metabolic cost of carrying a double-strap golf bag may facilitate a reduction in fatigue and reduced mechanical stress. Golf bag transportation must therefore be recognized as a factor in reducing the risk of injury and improving playing performance.